Peningkatan Kompetensi Guru Dalam Pembelajaran Berdiferrensiasi Berbasis Produk - Cholifah Tur Rosidah; Rarasaning Satianingsih; Rudy Sumiharsono; Apri Irianto; Susilo Hadi (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Differentiated learning is essential to implement in the learning process. This urgency is because not all students' competencies, which include initial abilities and learning outcomes, are the same. Thus the learning needs are different. This training aims to increase teacher competency in product-based differentiation learning. Place of training at SDN 163 Gresik. The activity was attended by 58 participants representing teachers from Cluster 2 Gresik. Case studies, discussions, questions and answers, workshops, and mentoring are used to implement community service. This activity resulted in the design of product-based differentiated teaching modules. After training, the results showed that 25 people gained excellent understanding, 27 people gained good understanding, and 6 people gained sufficient understanding. In conclusion, it is important to carry out community service activities so that teachers can learn about differentiated learning well.